Incidencia del uso de guías didácticas de software educativo heurístico en el proceso enseñanza aprendizaje en los estudiantes de bachillerato en la asignatura informática del Colegio de Bachillerato Dr. José María Velasco Ibarra del cantón El Guabo, periodo lectivo 2014-2015. - Macias Calderon, Lisbeth Katherine (2015)
The education system has always been subject to criticism and questions about how to develop it, as well as the tools used to meet the objective of transforming the individual, with the vision and desire, of course, to convert the teaching-learning in a more efficient process.